China's Future - Shambaugh, David (Cambridge Polity Press, 2016)
China's future is arguably the most consequential question in global affairs. Having enjoyed unprecedented levels of growth, China is at a critical juncture in the development of its economy, society, polity, national security, and international relations.
Include Figures, Notes and Index.
Keywords: China -- Diplomatic relations -- Politics and government